Cover Picture. Issue 6 (December 2014) - Unknown
<x xml:space="preserve">Abstract</x> In addition to Personal Accounts and world records, this issue features the Nozoe Autograph Book series. All Essays and the interactive website for the Nozoe Autograph Book project are found at: www.tcr.wiley‐vch.de/nozoe. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>